PERILAKU TENAGA KESEHATAN DENGAN KEPATUHAN MENGGUNAKAN ALAT PELINDUNG DIRI SESUAI STANDART OPERATING PROCEDURE DI RUANG RAWAT INAP RSUD MARIA WALANDA MARAMIS MINAHASA UTARA - Juita Maria Rori; Bongakaraeng Bongakaraeng; Marlyn M. Pandean (Jurnal Kesehatan Lingkungan, 2018)
Occupational health and safety is an instrument that protects workers, companies, the environment, and the surrounding community from the dangers of accidents. Health and safety aims to prevent, reduce, even nullify the risk of work accident (zero accident) .The purpose of this study was to determine the Behavior of Health Personnel With Compliance Using Personal Protective Equipment according to Standard Operating Procedures in Inpatient Room Maria Walanda Maramis Regional Hospital 2017. This research is an analytic observation research using Case Control Study design. The population in this research is all health workers in the hospital ward of Maria Walanda Maramis General Hospital which amounts to 60 people. Samples are all population numbers and determined by using total sampling technique that is as many as 30 people who meet inclusion criteria. Data were analyzed by Chi-Square test. The results of this study indicate that there is no correlation between knowledge of health personnel with compliance using Personal Protective Equipment according to Standard Operational Procedure at Regional General Hospital Maria Walnda Maramis (p = 0,232). There is no correlation between attitudes of health workers with compliance using Personal Protective Equipment according to Standard Operational Procedures at Maria Walanda Maramis Regional General Hospital (p = 1,000). There is no correlation between the actions of health personnel with compliance using Personal Protective Equipment according to Standard Operating Procedures at the Regional General Hospital of Maria Walanda Maramis (p = .0,481). Conclusion There is no significant correlation between knowledge, attitudes and actions of health personnel with compliance with Personal Protective Equipment according to Standard Operational Procedure Standard at Maria Walanda Maramis Regional Hospital in 2017.